"Double Maisonneuve fracture": an unknown fracture pattern - Kašper, Štěpán; Bartoníček, Jan; Rammelt, Stefan; Kamin, Konrad; Tuček, Michal (European journal of trauma and emergency surgery, 2022)
PURPOSE: The aim of this study was to describe pathoanatomy and to raise awareness of a fracture of the lateral malleolus combined with a high subcapital fracture of the fibula caused by a dislocation mechanism. METHODS: The study comprised 11 patients, 5 men and 6 women, with the mean age of 57 years (range, 21-87), with a "Double Maisonneuve fracture". Individual lesions of ankle structures were described on the basis of radiographs, CT, and intraoperative findings. RESULTS: The distal fibular fracture was classified as Weber type B in 1 case and Weber type C in 10 cases. The proximal fibular fracture was described as a subcapital oblique spiral fracture with metadiaphyseal involvement in nine cases and a high short oblique fracture with fibular head involvement in two cases. Injury to the deltoid ligament was revealed in six cases; a bicollicular fracture of the medial malleolus was found in five patients. Posterior malleolar fractures were classified as type 1 in eight cases and type 2 in three cases. Avulsion of the Chaput tubercle was detected in four cases. Injury to the interosseous tibiofibular ligament was assessed in nine patients. CONCLUSION: Double Maisonneuve fracture is a rare but probably underreported injury that must be taken into consideration during examination, as it may be easily overlooked. The essential part of diagnosis is a careful clinical examination and radiological assessment of the lower leg with additional CT examination of the ankle.
Keywords: Trimalleolar fractures; Ankle Fractures; Maisonneuve fracture; poranění kotníku; Female; fibula; Anterior malleolus; ženské pohlaví; Ankle fractures; lidé; Tibia; mnohočetné fraktury; Posterior malleolus; Middle Aged; Fractures, Multiple; Fibula; Male; Tibiofibular syndesmosis; tibie; Ankle Joint; vnitřní fixace fraktury; lidé středního věku; mužské pohlaví; Ankle Injuries; Fracture Fixation, Internal; hlezenní kloub; fraktury kotníku; Humans